Cardiorenal Syndrome in Acute Heart Failure Syndromes - Mohammad Sarraf; Robert W. Schrier (International Journal of Nephrology)
Impaired cardiac function leads to activation of the neurohumoral axis, sodium and water retention, congestion and ultimately impaired kidney function. This sequence of events has been termed the Cardiorenal Syndrome. This is different from the increase in cardiovascular complications which occur with primary kidney disease, that is, the so-called Renocardiac Syndrome. The present review discusses the pathogenesis of the Cardiorenal Syndrome followed by the benefits and potential deleterious effects of pharmacological agents that have been used in this setting. The agents discussed are diuretics, aquaretics, natriuretic peptides, vasodilators, inotropes and adenosine α1 receptor antagonists. The potential role of ultrafiltration is also briefly discussed.